2017
DOI: 10.1177/0018578717738080
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Prescription Pattern and Compliance to JNC 7 and JNC 8 at Tertiary Care Government Hospital, Hyderabad, India: A Cross-sectional Retrospective Study

Abstract: The monitoring of hypertension treatment can provide insight into the rational drug use pattern. The objective of this study was to examine the antihypertensive medication use among South Indian adults with hypertension in compliance with the hypertension treatment guidelines (Seventh Joint National Committee [JNC 7] and JNC 8). A total of 550 hypertensive people aged>25 years were included in this retrospective cross-sectional study. The order of drugs prescribed in the year 2012 was beta blockers (BB) > calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
4
5
0
Order By: Relevance
“…The analysis of this study population shows that 53% had CAD, 46.6% had diabetes, 42% had dyslipidemia, 13.4% had hypothyroidism, 5.8% had CKD, and 5.2% had Stroke. Akintunde et al also found similar result in their study [13].…”
Section: Anuradha Et Alsupporting
confidence: 78%
“…The analysis of this study population shows that 53% had CAD, 46.6% had diabetes, 42% had dyslipidemia, 13.4% had hypothyroidism, 5.8% had CKD, and 5.2% had Stroke. Akintunde et al also found similar result in their study [13].…”
Section: Anuradha Et Alsupporting
confidence: 78%
“…Although thiazide-type diuretics were recommended as initial therapy for most patients [ 37 ], it was observed that the prescription proportion was fairly lower than that of ARBs and CCBs in the current study. The low preference for diuretics may be related to their adverse effects such as hypokalaemia.…”
Section: Discussionmentioning
confidence: 55%
“…The thiazide diuretics were the least prescribed medicine, thus deviating from the JNC guidelines. They concluded that the combination therapy regimen must be followed as stipulated in the guidelines for the achievement of appropriate blood pressure goals [10]. It should, however, be noted that combination therapies predispose patients to drug therapy problems, especially drug-drug interactions [11,12].…”
Section: Discussionmentioning
confidence: 99%